STRATEGI BERTAHAN PEDANGAN BARANG BEKAS GANG RENDAH DITENGAH MARAKNYA ON-LINE SHOP - Wahyiah, Ita Rosita; Irwanto, Irwanto; Arifin, Suherman (Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2023)
The aim of this research is to analyze and examine how the traders survive and since when do second-hand goods traders gather in the low alleys to sell used goods that are not affected by online shops that are rife in the era of modernization and globalization. Using a descriptive qualitative method with data collection techniques, observation, interviews, and documentation. While the theory that the researcher uses is the theory of Pierre Felix Bourdieu with the theory of social practice which consists of Habitus, Arena and Capital. The results of this study show that this business has been around for decades, where the low alley located in front of ethnic Chinese shops is used as a place to sell by spreading merchandise on mats or tarpaulins, buyers and sellers transact while squatting or sitting on the floor. sidewalk. based on primary data sources collected from the first source (traders) through questionnaires and direct interviews. Researchers get the result that traders of used goods that are still suitable for use are sought after by consumers for various reasons including 1. Prices are very affordable, 2. Goods are still usable, 3. Goods according to needs, 4. Fun interactions, 5. Inter-ethnic assimilation, 6. There is historical value. The low alley has existed since the Dutch Colonial era. Although the goods in the lower alley are classified as second-hand goods, the quality is still quite good. Usually the traders start opening stalls from 09.00 to 17.00, open every day